STRANGULATED INCISIONAL HERNIA DUE TO BOWEL OBSTRUCTION CAUSED BY GALL ILEUS IN THE LATE POSTOPERATIVE PERIOD OF BILIODIGESTIVE SURGERY DUE TO IATROGENIC INJURY OF THE BILIARY DUCT: CASE REPORT - Alves, Michaela Helena Moretto; Guimarães, Bruna Mazzetto; Pareja, Helen Brambila Jorge (Seven Editora, 2025)
Case presentation: A 63-year-old man was admitted to the emergency room with severe abdominal pain for 1 week, associated with loss of appetite. He denied nausea, vomiting, and/or changes in bowel habits. He had undergone cholecystectomy 5 years earlier, which developed iatrogenic bile duct injury, requiring a new surgical approach for biliodigestive anastomosis during the same admission. With a suspected diagnosis of acute obstructive abdomen (AOA), an acute abdominal radiograph (X-ray) was performed, revealing distended bowel loops with an air-fluid level. Further investigation included abdominal computed tomography (CT), which revealed previous cholecystectomy with air-biliary obstruction, homogeneous splenomegaly, and distended bowel loops with an air-fluid level in the supraumbilical midline, consistent with acute obstructive abdomen due to an incarcerated hernia. Laboratory tests showed: TGO 119, TGP 199, FA 400, GGT 502, AM 243, CR 1.2. The patient underwent exploratory laparotomy. Intraoperatively, a strangulated incisional hernia was diagnosed due to obstructive acute abdomen caused by gallstone ileus. Band lysis was performed with enterectomy of the perforated segment of the strangulated hernia. The gallstone was removed from the biliopancreatic loop of the "roux-y", the biliodigestive anastomosis was re-performed, and the incisional hernia was surgically repaired. The patient was placed on a regular diet on postoperative day 2 and discharged on day 5. Discussion: The association between gallstone ileus and strangulated incisional hernia represents a rare but challenging presentation of obstructive acute abdomen. Gallstone ileus, characterized by the impaction of a gallstone in the intestinal tract, can occur even in cholecystectomized patients, especially those undergoing biliodigestive anastomoses or with spontaneous biliary-enteric fistulas. The presence of gallstones passing through the intestinal lumen can, in itself, generate obstruction in areas of reduced caliber, such as the terminal ileum. However, when a loop of bowel containing the stone generates intestinal obstruction, leading to incarceration of a previously existing incisional hernia—usually resulting from previous abdominal surgeries—there is an additional risk of strangulation, worsening the clinical picture and requiring urgent surgical intervention. A strangulated incisional hernia, in turn, compromises the vascular supply to the herniated bowel loop, which can rapidly progress to ischemia and necrosis. If the bowel loop impacted by a gallstone is located within this hernia, the risk of complications increases significantly. This overlapping mechanical factors—stone obstruction and herniated entrapment—can obscure the initial diagnosis, hindering early identification of gallstone ileus. Final remarks: The coexistence of both pathologies requires a high degree of clinical suspicion and prompt decision-making to avoid adverse outcomes. Although rare, post-cholecystectomy gallstone ileus is a possible condition, especially in the presence of late biliary fistulas or biliary anastomoses. Recognition of this pathophysiology is essential for early diagnosis and appropriate surgical management, avoiding complications such as intestinal necrosis or abdominal sepsis. DOI: https://doi.org/10.56238/sevened2025.037-012